Analysis of international experience in using organizational changes to form strategic planning toolkit in a construction organization - Ivakhnenko, I.; Kuzmin, T.; Churylo, M.; Hyria, V. (Ways to Improve Construction Efficiency, 2024)
Strategic planning is an integral component of managing construction companies, particularly in the context of a highly dynamic market environment. Leveraging international experience in organizational change management enables the development of effective decision-making tools, enhances competitiveness, and ensures sustainable growth. Global practices demonstrate that organizational changes in the construction sector encompass structural transformations, business process improvements, and the implementation of innovative approaches and digital technologies. Applying this experience can significantly strengthen the potential of Ukrainian companies in achieving long-term strategic goals. Construction companies face numerous challenges, including economic instability, regulatory changes, fluctuating demand, and increasing competition. In such circumstances, strategic planning requires flexible tools capable of adapting to new realities. Examining successful cases of international companies helps identify the most effective approaches to change management, including the use of Agile methodologies, Lean Construction, BIM technologies, and digital platforms. These methods contribute to resource optimization, process transparency, and accelerated decision-making. Moreover, human capital management remains a critical aspect. International experience indicates that engaging employees in change processes, fostering a strong corporate culture, and investing in employee training significantly enhance the effectiveness of strategic initiatives. Effective change management also involves establishing project management offices (PMOs) to ensure coordination, monitor progress, and manage risks. An analysis of international practices highlights key stages of organizational change, including diagnosing the current state, defining strategic objectives, developing a change plan, managing the transformation process, and evaluating effectiveness. This comprehensive approach provides a clear view of transformation processes, enhancing the quality of management decisions. In conclusion, leveraging international experience to develop a strategic planning toolkit for construction companies serves as an effective means of ensuring long-term resilience and competitiveness. Thoroughly studying and adapting best practices facilitates the creation of flexible management models that can swiftly respond to external challenges and foster sustainable company growth.